Combinatorial Effect of ARTP Mutagenesis and Ribosome Engineering on an Industrial Strain of Streptomyces albus S12 for Enhanced Biosynthesis of Salinomycin - Zhang, Kuipu; Mohsin, Ali; Dai, Yichen; Chen, Zhongbing; Zhuang, Yingping; Chu, Ju; Guo, Meijin (Frontiers in Bioengineering and Biotechnology, 2019)
Salinomycin, being an important polyketide has been widely utilized in agriculture, which inhibits the growth of pathogenic bacteria. Moreover, salinomycin has great potential in the treatment of cancer cells. Due to inherited characteristics and beneficial potential, its demand is also inclining. Therefore, there is a dire need to increase the current high demand of salinomycin. In order to obtain a high-yield mutant strain of salinomycin, the present work has developed an efficient breeding process of Streptomyces albus using atmospheric and room temperature plasma (ARTP) combined with ribosome engineering. In this study, the presented method has the advantage of significantly shorten mutant screening duration by using an agar block diffusion method as compared to other traditional strain breeding methods. In result, the obtained mutant Tet30Chl25 with tetracycline and chloramphenicol resistance gives salinomycin yield of 34712 mg/L in shake flask culture, which is over 2.0 folds than the parental strain S12. In addition, the comparative transcriptome analysis of low and high yield mutants, and the parental strain revealed the mechanistic insight of biosynthesis pathways in which the metabolic pathways including butanoate metabolism, starch and sucrose metabolism and glyoxylate metabolism were closely related to salinomycin biosynthesis. Moreover, we also confirmed that the enhanced flux of glyoxylate metabolism via overexpression gene of isocitrate lyase (icl) promoted the salinomycin biosynthesis. Based on these results, it is successfully verified that the overexpression of transcription regulator orf3, orf15 genes located in salinomycin synthesis gene cluster and crotonyl-CoA reductase gene (crr) are possibly responsible to increase the salinomycin production in a typical strain Streptomyces albus DSM41398. Conclusively, a tentative regulatory model of ribosome engineering combined with ARTP in S. ablus is proposed to explore the role of transcriptional regulators and stringent responses in the biosynthesis regulation of salinomycin.